Challenges of Pasture Feeding Systems—Opportunities and Constraints - Wróbel, Barbara; Zielewicz, Waldemar; Staniak, Mariola (Agriculture (Basel), 2023)
Grazing plays an important role in milk production in most regions of the world. Despite the importance of grazing, current trends in livestock farming in Europe are causing a decline in the popularity of pasture-based feeding of dairy cows. This paper aims to provide an overview of the challenges faced by the pasture feeding system under climate change. Grazing lands provide ecosystem services including regulation and storage of water flows, nutrient cycling, and C sequestration. Livestock grazing is the most important factor shaping and stabilizing pasture biodiversity. Some opportunities for pasture feeding are the health-promoting and nutritional qualities of milk and milk products, especially milk from pasture-fed cows. The beneficial effects of pasture feeding on animal health and welfare are not insignificant. Available organizational innovations can help better manage livestock grazing and, above all, better understand the impact of the grazing process on the environment and climate change.